Female wage profiles: An additive mixed model approach to employment breaks due to childcare - Torben Kuhlenkasper; Göran Kauermann (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
The paper investigates female wage profiles in West-Germany between 1984 and 2008 using data from the German Socio Economic Panel. The empirical study focuses on the short-run wageloss due to childcare and the long-run wage-profile in post-birth employment, respectivly. This is compared with wage profiles from females who are not mothers. As statistical analysis tool Additive Mixed Models are employed and estimated seperatetly for different levels of educational achievements. The models are dynamic in that main covariate effects are allowed to vary smoothly with working experience. The intention of the paper is to demonstrate with state of the art statistical models how wages are affected by labour market experience, employment interruptions and other covariates. The educational level of the mother and the time off the job influence the amount of wageloss and the wage profile afterwards. Labour market experience, as one major determinant of human capital, influences wages heavily and follows a dynamic patter.
Keywords: C14; C23; J13; J24; J31; 330; Additive Mixed Models; Dynamic Effects; Maternity Leave; Panel Data; Employment Interruption; Wage Profiles; Female Labour Supply